Exporting Vietnam’s Coconut Products: Opportunities and Threats - Nguyen, Thi Huong Giang; Nguyen, Minh Long; Nguyen, Thu Bao Minh (International Journal of Scientific Research and Management (IJSRM), 2024)
After highlighting the importance of Vietnam’s coconut product export industries, the research summarizes the prominent features of Vietnam's coconut products, the export procedures, and the export turnover of these products. It also identifies the opportunities and threats for Vietnam's coconut products. Specifically, opportunities for exporting Vietnam's coconut products include: (i) Large-scale production; (ii) Broad consumer market; (iii) Product processing technology; (iv) Support from coconut associations and traditional craft villages. On the other hand, the threats for exporting Vietnam's coconut products include: (i) Food safety issues; (ii) Competition with foreign countries; (iii) Production technology; (iv) Raw material market - product consumption market. The research results serve as a basis for the research team to consider and propose solutions from the government, associations, and enterprises to promote the export of Vietnam's coconut products.